Improving Adiabatic Film-cooling Effectiveness using a chevron shape ramp - Grine Mustapha1, Ben Ali kouchih fatima; Boualem khadidja; Fekire Halima; Azzi Abbès (Universty of El-oued جامعة الوادي, 2019)
In this study two geometrical configurations are considered for purpose comparison, which are the base line case, and the case with an upstream chevron with rounded edge. The ensemble-averaged Navier Stokes equations closed by the k-ε RNG turbulence model and standard wall function are used in frame of the finite volume method, computational Fluid Dynamic (CFD) code represented by the commercial programmers ANSYS CFX 14.0. The work consists of a numerical computation study of a film cooling on a flat plate. The goal is to verify the effectiveness of the present code by applying the same boundary conditions on the same geometry. Furthermore, another dimension of the physical domain was displayed by adding the concept of upstream chevron fence. Three blowing ratios are considered (0.50, 1.00, and 1.50) and length-to-diameter ratios 1.75. Results are shown in form of centerline adiabatic film cooling effectiveness .The most important element in this study is the film cooling effectiveness. This variable will be the subject of most of the results in this work
Intervention
Keywords: ilm cooling; Chevron; Upstream Chevron; Spanwise; CRVS; Anti CRVS